EMPLOYEE LOYALTY INFLUENCED BY LEADERSHIP AND JOB SATISFACTION AT CV PUTRA PERKASA MALANG - Christian Hannystia Putra; Sahala Manalu; Felik Sad Windu Wisnu Broto; I Gusti Ngurah Agung Arya Bhakta Narayana (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The purpose of this study was to determine the effect of leadership style and job satisfaction. This study uses a quantitative descriptive analysis approach with an explanatory design, which aims to test the hypothesis related to the effect of leadership style and job satisfaction on employee loyalty at CVA Putra Perkasa Malang. The dependent variable is employee loyalty, while the independent variables include leadership style and job satisfaction. Data were collected through a questionnaire with 80 respondents from the production department. This study uses a saturated sampling technique, and the data obtained were analyzed using validity, reliability, and multiple linear regression tests to test the effect of independent variables on the dependent variable. Classical assumption tests such as normality, multicollinearity, and heteroscedasticity were also carried out to ensure a valid regression model, followed by the t-test and F-test to test partial and simultaneous effects. The coefficient of determination (R²) is used to measure the strength of the relationship between the independent and dependent variables. The results of the study indicate that leadership style has a positive effect on employee loyalty at CV Putra Perkasa, which means that the better the leadership style applied, the higher the level of employee loyalty. In addition, job satisfaction also has a positive effect on employee loyalty, where employees who are satisfied with their jobs tend to have higher loyalty to the company. Simultaneously, leadership style and job satisfaction have a significant effect on employee loyalty, indicating that these two variables, both separately and together, play an important role in increasing employee loyalty at CV Putera Perkasa